PENGARUH PENERAPAN METODE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH PESERTA DIDIK KELAS X TKR 1 SEMESTER GENAP DI SMK SWASTA GKPS 2 PEMATANGSIANTAR TAHUN AJARAN 2023/2024 - Elis Triance Damanik; Hisarma Saragih; Ulung Napitu (Jurnal Pendidikan Sejarah Humaniora dan Ilmu Sosial, 2026)
Snowball Throwing Learning is a cooperative learning model where this method is implemented by dividing students into several groups, where each group member makes a question on a piece of paper and forms it like a ball, then the ball is thrown to other students for a specified time duration, which then each student answers the question from the ball they get. The results of this study indicate that the learning outcomes of students using the Snowball Throwing learning method are better than those who do not use the Snowball Throwing learning method. This can be seen from the average post-test score in the control class is 70.30. While the average post-test score in the experimental class is 80.30. Then from the hypothesis test shows the results of the Sig. (2-tailed) value is 0.00 meaning the Sig. (2-tailed) value is 0.05. So it can be concluded that there is a significant difference between learning outcomes in the experimental class and the control class. This shows that the application of the Snowball Throwing method has an influence on student learning outcomes with the research hypothesis stating that, "The application of the Snowball Throwing learning method can improve the history learning outcomes of class X students at SMK Swasta GKPS 2 Pematangsiantar" is accepted.